1977
DOI: 10.1002/1097-0142(197706)39:6<2470::aid-cncr2820390625>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Cystadenoma of the pancreas:An ultrastructural study

Abstract: A case of cystadenoma of the pancreas was studied at the light (LM) and the ultrastructural (EM) levels. The observation made under LM that the flattened epithelial cells lining the cystic spaces were similar to the centroacinar cells of a normal pancreas was supported by EM findings. Numerous glycogen granules were demonstrated in the cells, a feature characteristic of fetal but not adult centroacinar cells. A few epithelial cells contained occasional membrane bound dense granules of unknown nature. This obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In their detailed and well illustrated electron microscopic study of one cystadenoma, Lo et al (1977) concluded that the ultrastructure of the neoplastic cells was similar to that of normal centroacinar cells. A somewhat similar conclusion was drawn by Compagno & Oertel (r978), but their ultrastructural findings were based on formalin fixed material from two cases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In their detailed and well illustrated electron microscopic study of one cystadenoma, Lo et al (1977) concluded that the ultrastructure of the neoplastic cells was similar to that of normal centroacinar cells. A somewhat similar conclusion was drawn by Compagno & Oertel (r978), but their ultrastructural findings were based on formalin fixed material from two cases.…”
Section: Discussionmentioning
confidence: 98%
“…The ultrastructure of pancreatic cystadenoma has been the subject of only one detailed study which was a single case report (Lo et a/. 1977).…”
Section: Discussionmentioning
confidence: 99%